PENGARUH PENGGUNAAN E-COMMERCEDAN PENGADAAN BARANG TERHADAP KINERJA DIVISI PURCHASING PT DISTRIBUTOR GADGET - Rizal Rahmawan Rahmawan; Andi Muh. Rudhan Muh. Rudhan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the "Effect of the Use of E-Commerce and Procurement of Goods on Performance. The subject of this research is the Purchasing Department at PT.Distributor Gadget Indonesia. The population used in this study were 41 employees who were directly or indirectly involved in the process of using e-commerce and procuring goods. Data analysis in this study used SPSS version 20 software. The results of this study can be concluded that E- Influential Commerce significantly positive on performance (Y) either partially or simultaneously. Partially, the significance value of the E-commerce variable (X1) is 0.002 and the procurement process (X2) is 0.043. Simultaneously, the significance value of the E-commerce variable (X1) and the procurement process (X2) on performance (Y) is equal to 0.000. The results of the analysis of the coefficient of determination (R2) show that the performance variable (Y) can be explained through the E-commerce variable (X1) and the procurement process (X2) of 50%. While the rest is explained by other factors or variables not explained in this study, for example information sharing, process integration, and long term relationships between suppliers and buyers/consumers. Suggestions from this study are that companies, especially divisions related to the procurement process, are expected to be able to see opportunities and potentials caused by technological developments. One example of the impact of technological developments is the presence of E-commerce in the procurement process. Companies also need to understand the principles and issues arising from the use of E-commerce in the procurement process to maintain benefits, gain opportunities, and achieve the expected performance.